2020
DOI: 10.1161/atvbaha.120.314513
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Heart and Vasculature

Abstract: The coronavirus disease 2019 (COVID-19) pandemic presents an unprecedented challenge and opportunity for translational investigators to rapidly develop safe and effective therapeutic interventions. Greater risk of severe disease in COVID-19 patients with comorbid diabetes mellitus, obesity, and heart disease may be attributable to synergistic activation of vascular inflammation pathways associated with both COVID-19 and cardiometabolic disease. This mechanistic link provides a scientific framework for translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 111 publications
1
19
0
Order By: Relevance
“… 6 , 7 Evidence has linked complications of SARS-CoV-2 to the heart. 8 , 9 At presentation of COVID-19 disease, elevated levels of cardiac troponin have been observed, which are indicators of cardiac involvement and harbingers of poor outcome. 10 SARS-CoV-2 may directly infect human cardiomyocytes.…”
Section: Covid-19: Properties and Cellular Interactionsmentioning
confidence: 99%
“… 6 , 7 Evidence has linked complications of SARS-CoV-2 to the heart. 8 , 9 At presentation of COVID-19 disease, elevated levels of cardiac troponin have been observed, which are indicators of cardiac involvement and harbingers of poor outcome. 10 SARS-CoV-2 may directly infect human cardiomyocytes.…”
Section: Covid-19: Properties and Cellular Interactionsmentioning
confidence: 99%
“…Common atherosclerotic manifestations reported by patients with COVID-19 infection include a minor respiratory syndrome, hypoxemia, ischemic stroke, and inflammatory thrombophilia which may include thromboembolism [37,44,45,46]. Other cases reported include an increase in serum cardiac biomarkers such as troponin, ST-segment-elevation myocardial infarction and acute myocarditis based on clinical discoveries using elevated biomarkers, cardiac magnetic resonance imaging and electrocardiographic changes [47,48,49].…”
Section: Impact Of Covid-19 On Atherosclerosismentioning
confidence: 99%
“…Other cases reported include an increase in serum cardiac biomarkers such as troponin, ST-segment-elevation myocardial infarction and acute myocarditis based on clinical discoveries using elevated biomarkers, cardiac magnetic resonance imaging and electrocardiographic changes [47,48,49]. Children with harsh symptoms of COVID-19 were found to have vasculitis similar to Kawasaki disease [46,50,51,52,53,54]. The Sars-CoV-2 virus which triggers an inflammatory response in patients with COVID-19 also enhances the activation of platelets and the expression of tissue factor in these patients [46,55,56].…”
Section: Impact Of Covid-19 On Atherosclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes is one of the critical factors in the development of atherosclerosis. This fact is even relevant to the pandemic of coronavirus disease 2019 (COVID-19), as recent reports showed that patients with diabetes mellitus (DM) and atherosclerosis are at a greater risk for severe COVID-19 complications [ 3 ]. Therefore, it is essential to understand the mechanism underlying the development of atherosclerosis as diabetes progresses.…”
Section: Introductionmentioning
confidence: 99%